The Performance of Chitosan-based Activated Carbon for Supercapacitor Applications towards Sustainable Energy Technologies - Abu S.M.; Ansari M.N.M.; Al-Shetwi A.Q.; Muttaqi K.M.; Hannan M.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
In sustainable technologies, the application of supercapacitors (SC) for energy conversion and storage systems is rapidly increasing. Supercapacitors are widely employed in applications that require fast charge and discharge phases, such as in the automobile industry, where they are utilized in energy storage. Chitosan (CS) is a natural polymer material utilized in supercapacitor fabrication. Interest in supercapacitors is due to their high-energy capacity, storage for a shorter period, and longer lifetime. In this research, the fabrication of symmetric supercapacitors with activated carbon (AC) electrodes has been investigated in order to analyze their performance characteristics. AC is derived from CS biomass, which has remarkable biodegradability. It has been chemically activated using ZnCl2 as the activating agent. CS has been activated inside a furnace at 500, 600, and 700 C in an inert N2 atmosphere. A 1M aqueous potassium hydroxide (KOH) solution is used as the electrolyte. The test using electrolytes (KOH) revealed that the electrode's specific capacitance was 74.7 Fg-1, the highest value discovered. However, using organic electrolytes would have produced better results that can be used as a guide for future advancements. The influence of activation temperature on the porous characteristics of prepared AC was investigated utilizing surface area and pore size analyses. The morphological characteristics of synthesized AC were analyzed through scanning electron microscopy (SEM) and Energy Dispersive X-Ray Analysis (EDX). Symmetric SC electrodes fabricated is analyzed in a two-electrode system applying standard electrochemical characterization methods using the potentiostat. Symmetric SC electrodes fabricated are analyzed in a two-electrode system applying standard electrochemical characterization methods using the potentiostat. 1972-2012 IEEE.